Antioxidants Promote Intestinal Tumor Progression in Mice - Zhiyuan V. Zou; Kristell Le Gal; Ahmed E. El Zowalaty; Lara E. Pehlivanoglu; Viktor Garellick; Nadia Gul; Mohamed X. Ibrahim; Per-Olof Bergh; Marcus Henricsson; Clotilde Wiel; Levent M. Akyürek; Martin O. Bergo; et al. (MDPI AG, 2021)
Dietary antioxidants and supplements are widely used to protect against cancer, even though it is now clear that antioxidants can promote tumor progression by helping cancer cells to overcome barriers of oxidative stress. Although recent studies have, in great detail, explored the role of antioxidants in lung and skin tumors driven by RAS and RAF mutations, little is known about the impact of antioxidant supplementation on other cancers, including Wnt-driven tumors originating from the gut. Here, we show that supplementation with the antioxidants N-acetylcysteine (NAC) and vitamin E promotes intestinal tumor progression in the ApcMin mouse model for familial adenomatous polyposis, a hereditary form of colorectal cancer, driven by Wnt signaling. Both antioxidants increased tumor size in early neoplasias and tumor grades in more advanced lesions without any impact on tumor initiation. Importantly, NAC treatment accelerated tumor progression at plasma concentrations comparable to those obtained in human subjects after prescription doses of the drug. These results demonstrate that antioxidants play an important role in the progression of intestinal tumors, which may have implications for patients with or predisposed to colorectal cancer.